The Documentary Credit (processing And Domiciliation): Agb Bank And Sarl Ftb Import As A Case Study - طورش , زينب; طورش , بلقيس (khazzartech الاقتصاد الصناعي, 2023)
Nowadays, the growth of the international trade has resulted many risks that concerns the international trading which are rising and imposing a lot of pressure on suppliers, and leads the business world to use documentary credit. The documentary credit is known to be one of the most trusted methods in international payments due to the high level of satisfaction of its customers, and the diversity of it offers that make the process of importing much easier and balanced for sides, the importer and the exporter. The importer for a reasons of security and quality of operations mode, runs for the bank as his first option as an intermediary between the importer and the supplier thanks to its secure way of negotiation and commercial contracts. For the bank, to open the documentary credit, it is obliged to examine the documents presented to it by the beneficiary seller to verify the extent of their compliance with the instructions of the one who ordered the opening of the credit.